2017
DOI: 10.3389/fnagi.2017.00399
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Dysfunction Precedes Cognitive Decline and Neurodegeneration in Diabetic Insulin Resistant Mouse Model: An Implication for Causal Link

Abstract: Diabetic insulin resistance and pro-diabetic diet are reported to increase dementia risk through unknown mechanisms. Emerging evidence suggests that the integrity of blood-brain barrier (BBB) is central to the onset and progression of neurodegeneration and cognitive impairment. Therefore, the current study investigated the effect of pro-diabetic diets on cognitive dysfunction in association to BBB integrity and its putative mechanisms. In C57BL/6J mice chronically ingested with a diet enriched in fat and fruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 62 publications
(66 reference statements)
5
109
0
1
Order By: Relevance
“…It was suggested that blood proteins and neurovascular units are mediators of cognitive impairment [59,60,61]. When we compared cognition between the treated groups, we confirmed a significant impaired cognitive function.…”
Section: Infiltration Of Peripheral Immune Cells To the Cns Under Infsupporting
confidence: 63%
“…It was suggested that blood proteins and neurovascular units are mediators of cognitive impairment [59,60,61]. When we compared cognition between the treated groups, we confirmed a significant impaired cognitive function.…”
Section: Infiltration Of Peripheral Immune Cells To the Cns Under Infsupporting
confidence: 63%
“…obesity and Alzheimer disease (AD), administration of an HFD induces cognitive impairment and accelerates AD pathology (Jeon et al, 2012;Takeda et al, 2010). Moreover, damage to blood-brain barrier permeability as well as increased palmitate levels in the brain have been observed in mice fed an HFD (Spinelli et al, 2017;Takechi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, emerging evidence correlates cognitive impairment and psychologic behaviors (Cabrera et al, ; Caceda, Griffin, & Delgado, ). It also has been suggested that blood proteins and impairments of the NVU can be mediators of cognitive dysfunction (Mogi & Horiuchi, ; Taheri et al, ; Takechi et al, ). When we compared cognition between the treated mouse groups, we found a significant cognitive deficit in C1INH ASO‐treated mice compared with control mice.…”
Section: Discussionmentioning
confidence: 99%